Synthetic-biology approach for plant lignocellulose engineering - Yoshida, Kouki; Sakamoto, Shingo; Mitsuda, Nobutaka (Plant Biotechnology, 2024)
Plant biomass is an abundant, renewable resource that offers multiple advantages for the production of green chemicals and recombinant proteins. However, the adoption of plant-based systems by industry is hindered because mammalian and other cell cultures are well-established and better characterized in an industrial setting, and thus it is difficult for plant-based processes to gain a foothold in the marketplace. Therefore, additional benefits of plant-based systems may be essential to tip the balance in favor of sustainable plant-derived products. A crucial factor in biomass valorization is to design mid- to high-value co-products that can be derived cost-effectively from the residual lignocellulose (LC). However, the utility of LC remains limited because LCs are, in general, too recalcitrant for industries to utilize their components (lignin, cellulose, and hemicelluloses). To overcome this issue, in planta engineering to reduce LC recalcitrance has been ongoing in recent decades, with essential input from synthetic biology owing to the complexity of LC pathways and the massive number of genes involved. In this review, we describe recent advances in LC manipulation and eight strategies for redesigning the pathways for lignin and structural glycans to reduce LC recalcitrance while mitigating against the growth penalty associated with yield loss.